Age‐related differences in practice‐dependent resting‐state functional connectivity related to motor sequence learning. Issue 2 (11th October 2016) - Mary, Alison; Wens, Vincent; Op de Beeck, Marc; Leproult, Rachel; De Tiège, Xavier; Peigneux, Philippe
Abstract: Decreased neural plasticity is observed with healthy ageing in the primary sensorimotor (SM1) cortex thought to participate in motor learning and memory consolidation processes. In the present magnetoencephalography study, the post‐training reorganization of resting‐state functional connectivity (rsFC) and its relation with motor learning and early consolidation in 14 young (19–30 years) and 14 old (66–70 years) healthy participants were investigated. At the behavioral level, participants were trained on a motor sequence learning task then retested 20–30 min later for transient offline gains in performance. Using a sensorimotor seed‐based approach, rsFC relying on beta band power envelope correlation was estimated immediately before and 10 min after the learning episode. Post‐training changes in rsFC (from before to after learning) were correlated with motor learning performance and with the offline improvement in performance within the hour after learning. Young and old participants exhibited differential patterns of sensorimotor‐related rsFC, bearing specific relationships with motor learning and consolidation. Our findings suggest that rsFC changes following learning reflect the offline processing of the new motor skill and contribute to the early memory consolidation within the hour after learning. Furthermore, differences in post‐training changes in rsFC between young and old participants support the hypothesis that ageing modulates the neural circuits underlying the learning of a new motor skill and the early subsequent consolidation stages. Hum Brain Mapp 38:923–937, 2017 . ©2016 Wiley Periodicals, Inc.